2018
DOI: 10.1007/s00706-018-2306-8
|View full text |Cite
|
Sign up to set email alerts
|

Methyl glycosides via Fischer glycosylation: translation from batch microwave to continuous flow processing

Abstract: A continuous flow procedure for the synthesis of methyl glycosides (Fischer glycosylation) of various monosaccharides using a heterogenous catalyst has been developed. In-depth analysis of the isomeric composition was undertaken and high consistency with corresponding results observed under microwave heating was obtained. Even in cases where addition of water was needed to achieve homogeneity—a prerequisite for the flow experiments—no detrimental effect on the conversion was found. The scalability was demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Exemplary results of this study are presented in Table 26 . Note that, for sugars that are unsolvable in MeOH, minimal amounts of water were added under flow conditions [ 46 ].…”
Section: Fischer Glycosylation In Reactorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exemplary results of this study are presented in Table 26 . Note that, for sugars that are unsolvable in MeOH, minimal amounts of water were added under flow conditions [ 46 ].…”
Section: Fischer Glycosylation In Reactorsmentioning
confidence: 99%
“…Note that, for sugars that are unsolvable in MeOH, minimal amounts of water were added under flow conditions [ 46 ].…”
Section: Fischer Glycosylation In Reactorsmentioning
confidence: 99%
“…Fischer glycosylations have already been successfully carried out in microreactors. It has been shown that similar yields are achievable as for example using microwave radiation, which is the current state of the art [23]. However, microwave-mediated processes suffer from their poor scalability and, in some cases with Fischer glycosylations, also from an explosion risk due to the existing headspace caused by the used and potentially flammable alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the development of a continuous process of Fischer glycosylation in the microreactor provides a promising basis for numberingup the process. [23]…”
Section: Introductionmentioning
confidence: 99%
“…Toward our aspirations in this area we recently reported the first short and fully scalable synthetic approach to l,d -heptose peracetate based on indium mediated acyloxyallylation of l -lyxose and demonstrated it on a >100 mmol (45 g) scale (Stanetty and Baxendale, 2015 ). We are currently developing methodology for the analogous preparation of d,d -heptose peracetate (Aronow et al, 2019 ), with the intention of paving the way to make both d - manno -heptoses commercially available as their crystalline, bench-stable pyranose peracetate derivatives. Availability, be it commercial or at least through synthetically straightforward chemistry, is however only the first piece of a much larger puzzle ( Scheme 1 , bottom-left).…”
Section: Introductionmentioning
confidence: 99%